2005
DOI: 10.1097/00041327-200503000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuropathy Associated With Linezolid Treatment

Abstract: Two patients undergoing long-term treatment with linezolid for pneumonia had decreased visual acuity, dyschromatopsia, and cecocentral scotomas characteristic of toxic optic neuropathy. Visual function slowly recovered 3 to 4 months after discontinuation of the antibiotic treatment in both patients. Toxic optic neuropathy may occur from linezolid. Early withdrawal of the antibiotic may be associated with visual recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 8 publications
0
27
1
1
Order By: Relevance
“…1,3,4,6,8 In contrast, MRI fi ndings in parts of the optic canal in the present patient showed high signal intensity in the optic nerve of the right eye before discontinuance of linezolid, with a slight reduction in signal intensity after discontinuance. Kurokawa et al 21 reported that short T1 inversion recovery magnetic resonance images show an increase in the frequency of high signal intensity in the optic nerve with aggravation of optic disc cupping.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…1,3,4,6,8 In contrast, MRI fi ndings in parts of the optic canal in the present patient showed high signal intensity in the optic nerve of the right eye before discontinuance of linezolid, with a slight reduction in signal intensity after discontinuance. Kurokawa et al 21 reported that short T1 inversion recovery magnetic resonance images show an increase in the frequency of high signal intensity in the optic nerve with aggravation of optic disc cupping.…”
Section: Discussioncontrasting
confidence: 90%
“…Early discontinuation of the antibiotic may be associated with a gradual, but not necessarily full, recovery of visual function. 6 Therefore, it is important for ophthalmologists as well as physicians and orthopedists to consider the possibility of optic neuropathy caused by long-term use of linezolid.…”
Section: Discussionmentioning
confidence: 99%
“…Linezolid reaches inhibitory concentrations for most gram-positive pathogens within 4 hours after a single oral dose of 600 mg (72). Toxicity has been associated with off label extended therapy of 5-50 months (73)(74)(75). Full visual recovery has been reported in some cases after discontinuing the drug (76); however, the peripheral neuropathy is often irreversible.…”
Section: Linezolidmentioning
confidence: 99%
“…Vision improved significantly in all patients after discontinuation of linezolid, providing support for the diagnosis of reversible linezolid-induced optic nerve toxicity. Five similar patients with evidence of linezolid-induced optic neuropathy are previously described [1][2][3] (table). Four additional patients with incomplete documentation likely had linezolid-induced optic neuropathy based on improvement in visual symptoms or evoked potentials after linezolid discontinuation [4][5][6][7] (see table).…”
mentioning
confidence: 99%